Goat milk composition at morning and evening milking - Kastelic, Miran; Kompan, Dragomir (Acta Agraria Kaposváriensis, 2006)
The differences in milk quantity and milk composition between morning and evening milking were studied in a model where the effects of administration of alpha linoleic, eicosapentanoic, and docosahexaenoic fatty acids, individual animal and lactation period were included. The effects of animal and lactation period significantly influenced all variables. Added fatty acids didn’t influence fat in milk. The percentage of milk ingredients (fats, proteins, lactose, dry matter without fats and total dry matter) did not differ between morning and evening milking. Average time period between morning and evening milking was thirteen hours and the quantity of milk and milk ingredients was larger at evening, but the production of milk ingredients per time period was faster in the shorter night period.